(untitled) (Islamic Sciences Journal, 2023)
Praise be to God as great as the number of His creation, the contentment of Himself, the weight of His Throne, and the extent of His words, and prayers and peace be upon the most honorable of His creation and the seal of the prophets, the Chosen One, Muhammad, and upon his family and his good and pure companions, and after… The selection of this topic is to deal deeply with of the history of this ancient city and the important era, namely from the economic side, through the book of Sahih Al-Bukhari, which is considered one of the important, comprehensive and correct hadith books especially it included hadiths with economic which has an effect on the life of the Islamic community. The researcher also tried to write about an aspect of the main aspects of Islamic civilization in which Islam’s supremacy and its richness in financial and economic policy becomes clear and evident, and how its provisions reformed economic conditions and financial systems removed the injustice that was the distinguishing feature of previous eras, and its repercussions on social conditions. The political and intellectual, as well as the importance of the place and the historical era, which is considered one of the brightest eras of Islam. It also deals the agricultural activity, and discussed the issues that Islam dealt with to reform the agricultural aspect, and then reviewed the most important agricultural crops. It also dealt tackled the industrial activity, and reviewed the most important industries at that time. This paper also sheds light on commercial activity. The role of immigrants in promoting the commercial process in the city is also shown, as well as reviewing the most important trades that took place in it. It further clarified the role of Islam in organizing the commercial process in civil society, by controlling steadiness and weights, and finally a chapter is devoted to explain The process of browsing and raising animals.